HYBRID DIELECTRIC RESONATOR ANTENNA FOR C-BAND APPLICATION - Pathak, Deepika; Sharma, Sudhir Kumar; Kushwah , Vivek Singh (International Journal of Engineering Technologies and Management Research, 2018)
This article presents a triple band hybrid cylindrical Ring Dielectric resonator antenna. The proposed antenna consists of Ring Dielectric resonator antenna and has a reformed pentagon shaped slot antenna. By the help of HFSS simulation software this proposed antenna has been designed. The return loss of the proposed antenna is -16dB, -20dB, -15dB respectively at frequency of 4.7GHz, 6.1GHz, 7.5 GHz respectively. The proposed antenna is applicable for c-band applications.